THE EFFECT OF INJECTION OF INTRA ARTICULAR ALLOGENIC BONE MARROW MESENCHYMAL STEM CELL-PLATELET CELL RICH PLASMA (BMSCs-PRP) ON FULL-THICKNESS ARTICULAR CARTILAGE DEFFECT REGENERATION IN RABBIT - Taufik, S. Ahmad (Stem Cell Research and Development Center, Universitas Airlangga, 2018)
The joint cartilage defectfullthickness is still a problem today because its currenttreatment still has not delivered maximum results. Current treatment uses cartilage enginering using mesenchymal stem cells alone and or combining growth factor. The aim of this study was to investigate the effect of intra-articular injection of Allogenic bone marrow mesenchymal stem cell - Platelet rich plasma (BMSCs-PRP) on regeneration of cartilage defect fullthickness in rabbits. The design of this study was a post-test only control group design using 36 New Zealand white rabbits divided into three groups. Each group were treated with PRP, BMSCs and BMSCs-PRP. Results were evaluated after 10 weeks. In the evaluation, macroscopic images showed the best healing in the BMSCs-PRP group. Histopathologic examination showed that in the MSCs-PRP group, there was a significant increase in the number of chondrocytes (p = 0,000), cartilage area (p = 0,000), as well as the number of Agecoprogenitorexpec- tion cells (p = 0,000) and collagen type 2 (p = 0,000). BMSCs were able to differentiate into condroblasts which then synthesize aggressive and collagen type 2. Platelet rich plasma (PRP) contains growth factor BMP, TGF, FGF and IGF which can accelerate the occurrence of MSCs differentiation. Intra-articular injections Allogenic bone marrow mesenchymal stem cell (BMSCs-PRP) is able to regenerate and cure full-thickness joint cartilage defects through differentiation of MSCs into condroblasts.Keyword: Allogenic, Bone marrow Mesenchymal stem cell, Cartilage, Platelet rich plasma, Full-thickness.